Measuring 19F shift anisotropies and 1H–19F dipolar interactions with ultrafast MAS NMR - Martini, Francesca; Miah, Habeeba K.; Iuga, Dinu; Geppi, Marco; Titman, Jeremy J. (Elsevier, 2015)
A new 19F anisotropic–isotropic shift correlation experiment is described that operates with ultrafast MAS, resulting in good resolution of isotropic 19F shifts in the detection dimension. The new experiment makes use of a recoupling sequence designed using symmetry principles that reintroduces the 19F chemical shift anisotropy in the indirect dimension. The situations in which the new experiment is appropriate are discussed, and the 19F shift anisotropy parameters in poly(difluoroethylene) (PVDF) are measured. In addition, similar recoupling sequences are shown to be effective for measuring 1H–19F distances via the heteronuclear dipolar interaction. This is demonstrated by application to a recently synthesized zirconium phosphonate material that contains one-dimensional chains linked by H–F hydrogen bonds.